LAUDATO SÍ CHALLENGES IRRATIONAL RATIONALIZATION - Reginald Alva (Asian Horizons, 2020)
The contemporary world in the name of progress and development poses severe danger to the environment. The rich and the dominant are ruthlessly exploiting the natural resources for their selfish gains. Secularization is systematically destroying the moral order of the society. However, the political and the economic powers are justifying all these abuses under the garb of rationalization. Pope Francis through his encyclical Laudato Sí is challenging this irrational rationalization, which is one of the major causes of environmental degradation and moral depravity. In this paper, we shall examine the challenges and proposals, which Pope Francis is putting forward to build a harmonious world, where everyone feels accepted and loved.